Elucidation With the Protease α-Chymotrypsin of the Inhibitory Modulating Action of Endogenous Neuropeptide Y Over Sympathetic Neurotransmission in Rat Vas Deferens - Kageyoshi Ono; Akira Saito; Katsutoshi Goto; Yutaka Kasuya; Koki Shigenobu (Elsevier, 2003)
The physiological role of endogenous neuropeptide Y (NPY) in sympathetic neurotransmission was examined in rat and guinea pig vas deferens (VD), using α-chymotrypsin (α-cT). NPY-like immunoreactivity was detected in the longitudinal muscle layer of VD densely in rats but sparsely in guinea pigs, and it disappeared following surgical denervation. Under blockade of the prejunctional α2-adrenergic autoinhibition, α-cT potentiated the phasic contraction in rat, but not guinea pig, VD induced by trains of transmural nerve stimulation (TNS) in a frequency-dependent manner, which was reproducible during repeated applications and not affected by pretreatment with capsaicin. In contrast, α-cT did not potentiate the twitch response or contractions induced respectively by a single pulse TNS or by direct electrical stimulation to the smooth muscle. Exogenously applied NPY suppressed the twitch response, which was cancelled by α-cT, and excitatory junction potentials, although it affected neither spontaneous junction potentials nor the direct electrical stimulation-induced contraction. These observations provided further evidence to support that NPY is released endogenously by TNS at high frequency, acting prejunctionally to suppress sympathetic neurotransmission. Thus, the protease α-cT proved itself to be a useful tool to reveal a functional role of endogenously released peptides.